2014
DOI: 10.1161/hypertensionaha.114.03292
|View full text |Cite
|
Sign up to set email alerts
|

Office, Home, and Ambulatory Blood Pressures as Predictors of Cardiovascular Risk

Abstract: Abstract-Ambulatory blood pressure (BP) is considered as the gold standard of BP measurement although it has not been shown to be more strongly associated with cardiovascular risk than is home BP. Our objective was to compare the prognostic value of office, home, and ambulatory BP for cardiovascular risk in 502 participants examined in 1992 to 1996. The end point was a composite of cardiovascular mortality, myocardial infarction, stroke, heart failure hospitalization, and coronary intervention. We assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 31 publications
0
84
1
5
Order By: Relevance
“…At least 7 cohorts (5 general populations and 2 general practice populations) [4][5][6][7][8][9][10] have assessed longitudinal associations between home BP measures and incident CVD events (Table S1). They found that combined morning and evening SBP is associated with CVD events, independently of office SBP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At least 7 cohorts (5 general populations and 2 general practice populations) [4][5][6][7][8][9][10] have assessed longitudinal associations between home BP measures and incident CVD events (Table S1). They found that combined morning and evening SBP is associated with CVD events, independently of office SBP.…”
Section: Discussionmentioning
confidence: 99%
“…They found that combined morning and evening SBP is associated with CVD events, independently of office SBP. [4][5][6][7][8] Only COX analyses were conducted in these studies, [4][5][6][7][8][9][10] and thus the clinical utility of home BP measurement has remained uncertain. 23 This limitation was resolved in the present study, which evaluated the discrimination and recalibration of risk prediction models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 24 hours ambulatory systolic and diastolic BPs were also found to be independent predictors of CV events, including stroke, in another observational study of 502 patients in Finland with 16.1 years of follow up. 27 Several other ambulatory blood pressure parameters have been studied for prediction of cardiovascular events. In a meta-analysis of 13,844 patients with hypertension 28 comprising nine cohorts from Europe, Japan, and Brazil, nocturnal (nighttime) systolic BP independently predicted higher CV risk.…”
Section: Ambulatory Blood Pressure In Risk Assessment For Strokementioning
confidence: 99%